Pengaruh Good Corporate Governance dan Kinerja Keuangan terhadap Pengungkapan Islamic Social Reporting - Nur Hayati; Luluk Prihatiningsih (JRAK: Journal of Accounting Research and Computerized Accounting, 2021)
The aims of this study to determine the effect of good corporate governance and financial performance on the disclosure of Islamic social reporting on Islamic commercial banks in Indonesia. This research is a type of quantitative research. The population used in this study is to take Islamic Commercial Banks (BUS) which have been registered with Bank Indonesia for 6 years from 2013-2018. The number of samples tested was 60 annual financial reports (annual report) Islamic Commercial Banks (BUS) which were selected using the purposive sampling method. This study analyzes the annual financial statements of shariah banking with content analysis methods. This study uses descriptive analysis technique and multiple linear regression analysis. The result of this study showed that the variable frequency of the board commissioners meeting, the size of the shariah supervisory board, profitability and liquidity affect the disclosure of Islamic social reporting, where as the variable size of the board commissioners, the size of the audit committee and public ownership have no effect on the disclosure of Islamic social reporting. Keywords: ISR, GCG, Profitability, Liquidity, BUS